'The need for dose–response studies: time for a reminder?' – reply from the authors. (6th September 2020) - Buhl, T.; Geier, J.
Abstract : Linked Articles: Shuster. Br J Dermatol 2020; 183 :1148 . Heetfeld et al . Br J Dermatol 2020; 183 :139–145